Electrophysiological Subtypes and Prognostic Factors of Guillain-Barre Syndrome in Northern China - Tian, Jing; Cao, Cuifang; Li, Tong; Zhang, Kun; Li, Peifang; Liu, Yaling; Liu, Xiaoyun (Frontiers in Neurology, 2019)
Abstract Objectives: To assess the epidemiology of different electrophysiological subtypes of Guillain-Barre syndrome (GBS) and investigate the factors affecting the prognosis of the acute motor axonal neuropathy (AMAN) subtype in northern China. Methods: According to the National Institute of Neurological Disorders and Stroke diagnostic criteria for GBS, 104 consecutive GBS patients were recruited from the Department of Neurology of the Second Hospital of Hebei Medical University, China from 2014 to 2018. Results: Based on nerve conduction studies (NCSs), AMAN was the most common subtype in Northern China, accounting for 58 patients (55.8%). AMAN patients had significantly higher prevalence of antecedent diarrhea, longer duration of hospitalization, and slightly slower recovery than those with acute inflammatory demyelinating polyneuropathy (AIDP), but there was no statistical difference in disease severity or short-term prognosis between AMAN and AIDP. Based on multivariate regression analysis, AMAN patients with antecedent diarrhea (OR = 0.16, 95% CI: 0.03–0.756, p = 0.021) or conduction blocks (CBs) (OR = 0.033, 95% CI: 0.001–0.787, p = 0.035) had dramatically better short-term prognosis. Decreased compound action potential with distal stimulation (dCMAP) amplitude was associated with significant slower speed of recovery(OR = 8.31, 95% CI: 2.55–27.10, p = 0.02). Conclusion: AMAN is still the most common subtype of GBS in northern China. A decline in dCMAP amplitude is predictive factor of a slow recovery and poor outcome of GBS. Diarrhea and CBs may be the factors for better short-term prognosis in AMAN patients in Northern China.